Photosynthetic pigments in maize (Zea mays) vis-Ã -vis biological performance and host selection by Sesamia inferens - SAU, ASHOK K; DHILLON, MUKESH K (The Indian Journal of Agricultural Sciences, 2022)
In the present study, host selection behaviour and biological performance of Sesamia inferens on different maize (Zea mays L.) genotypes was investigated in 2018â€“19, and constitutive and insect damage-induced levels of various photosynthetic pigments were determined. There were significant differences in larval period, larval survival, larval weight, pupal period, pupal weight, adult emergence, and fecundity of S. inferens on the test maize genotypes. The S. inferens that fed on maize genotypes, viz. CPM 2, CPM 4, CPM 8, CPM 15 and CML 345 showed significant increase in developmental period, decrease in larval weight, and reduced larval survival, adult emergence and fecundity as compared to other test genotypes. The S. inferens larval recovery and preference were significantly lower, while the larvae took longer time to establish in the whorls of CPM 2, CPM 15 and CML 345 as compared to other test maize genotypes. The chlorophyll A, chlorophyll B and total chlorophyll content varied significantly in the seedlings of different maize genotypes, under healthy and S. inferens damaged conditions (except, chlorophyll B), while the genotype Ã— treatment interactions were non-significant. The differences for total carotenoids were non-significant. The S. inferens infestation reduced these photosynthetic pigments in the seedlings of all test maize genotypes, except Basi Local, with lowest reduction in CPM 2. The study suggests that the maize genotypes, viz. CPM 2, CPM 4, CPM 8, CPM 15 and CML 345 have greater detrimental effects on the development, survival and fecundity of S. inferens, and can be used in maize improvement program.